Snowmaking Development Trajectories in French Alpine Ski Resorts: The Influence of Local Specificities and Regional Support Policies - Lucas Berard-Chenu; Hugues François; Emmanuelle George; Samuel Morin (Revue de Géographie Alpine)
The specificities of mountain tourism areas and regional public policies influence the snowmaking equipment trajectories of ski resorts in the French Alps. Based on interviews among 20 ski resorts in Savoie (Northern French Alps) and data from regional policy of subsidies for snowmaking investments, this work analyses the drivers affecting the paths taken by ski resorts in their development of snowmaking. Access to water, climatic constraints and the expectations of local tourism stakeholders drive the development of snowmaking in each ski resort. The dependence of mountain tourism areas on the winter sports economy has led to the implementation of support policies for snowmaking by institutional actors. This study presents an overview of support policies in France and shows, through the case of the Auvergne-Rhône-Alpes region (NUTS-2), that between 2016 and 2019 subsidies have benefited the extension of snowmaking coverage in the largest ski resorts. This support from institutional stakeholders is one of the characteristics that illustrates a phenomenon of mountain tourism areas’ path dependence on the winter sports industry.